2014
DOI: 10.3892/mmr.2014.3015
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium depletes cellular iron availability through enhancing ferroportin translation via iron responsive element

Abstract: Abstract. Cadmium (Cd) is a heavy metal that has detrimental effects on various organs. The widespread contamination of Cd in the environment, crops and food sources poses a severe threat to human health. Acute toxicities of Cd have been extensively investigated; however, the health impact of chronic low-dose exposure to Cd, particularly exposure under non-toxic concentrations, has yet to be elucidated. Furthermore, the toxic threshold of Cd is currently unknown. Ferroportin is the only known iron exporter in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Similar results were obtained in the preneoplastic MCF 10A breast epithelial cells (unpublished data). Contrary to this observation, in macrophages Cd up-regulated FPN expression and depleted cellular iron availability (Sun et al, 2015). The different expression patterns of FPN upon Cd treatment might be due to the different functional properties of the cell types.…”
Section: Discussionmentioning
confidence: 89%
“…Similar results were obtained in the preneoplastic MCF 10A breast epithelial cells (unpublished data). Contrary to this observation, in macrophages Cd up-regulated FPN expression and depleted cellular iron availability (Sun et al, 2015). The different expression patterns of FPN upon Cd treatment might be due to the different functional properties of the cell types.…”
Section: Discussionmentioning
confidence: 89%
“…Meanwhile, Cd can impair erythropoietin synthesis in the kidney, resulting in an increase in hepcidin production and reduction of iron availability for erythropoiesis (Horiguchi, 2007). Our recent study found the expression levels of FPN could be up-regulated in macrophages upon exposure to sublethal Cd, and LIP was diminished (Sun et al, 2015). In another study by our group, we demonstrated that Cd could likely compete with ferrous iron to interact with the 5′-UTR iron response element of FPN's mRNA, affecting the translation of FPN (Sun et al, 2015).…”
Section: Cadmium (Cd)mentioning
confidence: 99%
“…Our recent study found the expression levels of FPN could be up-regulated in macrophages upon exposure to sublethal Cd, and LIP was diminished (Sun et al, 2015). In another study by our group, we demonstrated that Cd could likely compete with ferrous iron to interact with the 5′-UTR iron response element of FPN's mRNA, affecting the translation of FPN (Sun et al, 2015). Additionally, it has been suggested that Cd may regulate hepcidin-mediated iron homeostasis by inducing the secretion of IL-6 (Horiguchi et al, 2011).…”
Section: Cadmium (Cd)mentioning
confidence: 99%
See 1 more Smart Citation